Os saberes e as práticas dos professores do Ensino Fundamental - anos iniciais sobre a alfabetização cartográfica para a implementação da BNCC no território brasileiro - Dapper , Vanderson Rafael Muller (2021)
The Common National Curriculum Base (BNCC) is a normative document that defines the essential learning, as well as the competences and abilities that must be developed in basic schooling. Its implementation will guide the preparation of school curricula for public and private establishments, whether municipal, state or federal. By understanding that the BNCC does not exhaust the debates about the curriculum organization, nor does it solve the problems and gaps that were observed during the preparation of the document, with the research it will seek to analyze the inclusion of geographic contents related to cartographic literacy in the BNCC, in order to assess the organization of contents and identify the weaknesses in the teaching of Geography experienced by teachers in the Early Years of Elementary School. To this end, we analyzed the official documents that guide school curricula and the content of questionnaires answered by 600 teachers, distributed throughout all Brazilian states and who teach in this modality of education to understand how teachers in the Initial Years of Elementary Education are interpreting the contributions of the BNCC on cartographic literacy and ascertaining whether they will be prepared for its implementation in the coming years. Thus, it is observed from the research results that the development of cartographic literacy is far from being a reality for all Brazilian schools due to a set of factors that involve the working conditions and training of teachers in the Early Years of Elementary School. Therefore, it allows us to conclude that, in addition to the re-elaboration of school curricula according to the objects of knowledge present in the thematic unit on forms of representation and spatial thinking present in the BNCC, it is necessary for each Brazilian school, based on its educational reality, to identify and seek to overcome the weaknesses that make the success of cartographic literacy unfeasible.